EP380/#421 Perioperative glycemic management program (PGMP) pilot in a Canadian tertiary centre. (4th December 2022) - Kuzma, Tamara; Mckeen, Julie; Harrison, Tyrone; Brindle, Mary; Beesoon, Sanjay; Helmle, Karmon; Cameron, Anna; Ruzycki, Shannon
Abstract : Objectives: Postoperative hyperglycemia occurs in two-thirds of non-cardiac surgery patients and is associated with increased morbidity and mortality. We implemented a multi-disciplinary perioperative glycemic management pathway with the aim of reducing postoperative hyperglycemia and improving patient outcomes. Methods: Our study evaluated the implementation of the PGMP in gynecologic oncology patients. The PGMP encompasses glycemic management across the outpatient and inpatient surgical journey. We report changes in process measures (blood glucose measurement), outcome measures (hyperglycemia) and clinical measures (length-of-stay) pre- and post-implementation. Single-cohort interrupted time-series analysis was used to compare pre- (April 1, 2018 – September 30, 2019) and post- (October 1, 2019 – March 31, 2021) intervention means and trends. Results: 949 gynecologic oncology patients were evaluated pre-intervention, and 878 post. After implementation, the proportion of patients who were screened with HbA1c increased by 11.3% (95% CI: 5.0, 17.7%; p=0.02). The proportion of patients with diabetes who had at least one blood glucose measurement in the first 24-hours after surgery increased by 15.3% (95% CI: -3.2, 33.8%; p=0.10). Median length-of-stay for all postoperative patients decreased by 0.42 days (95% CI: -0.91, 0.07 days; p=0.09). There was no change in 30-day readmissions, regardless of diabetes diagnosis. Conclusions: Implementation of PGMP increased the identification of patients at high-risk for hyperglycemia. Our pilot reveals challenges experienced in evaluating perioperative glycemic management. Our study also showcases the need to measure both process and outcome measures and the need to perform robust statistical analysis when evaluating quality improvement initiatives.